International Cooperation Management: Case of Observatory of International Commerce and Foreign Investment of Otavalo University - Núñez Naranjo, Edwin Santiago; Orbes Revelo, Belky Nerea; González Alonso, Jesús Francisco (SATHIRI, 2022)
Economic funds from international cooperation have become an aid tool and a source of financing for research organizations located in developing countries, which do not have the necessary resources for their operation. The adjudication and management of this kind of funds have been a topic of interest for several investigation centers, such as the Observatory of Foreign Trade and Foreign Investment of the University of Otavalo, which has generated an investigative effort to identify a viable process that allows access to funds, from international organizations in a non-reimbursable modality, such as those offered by the Italo Ecuatoriano Fund for Sustainable Development. The methodology has been limited to a qualitative paradigm and it has focused on a descriptive level; a bibliographic analysis has been generated about the typology and existing international cooperation modalities, and 3 qualitative instruments have been applied for gathering field information, interviews with experts on the subject. As main result of the investigation it has been generated an applicable and replicable mechanism of access to non-reimbursable economic amounts from international organization, in particular from the Italo-Ecuadorian Sustainable Development Fund, for research activities in foreign trade and foreign investment. This mechanism is presented in a descriptive flow chart of the process that would serve as a guideline for other centers that require international assistance.